A UV pasteurization machine - Shamsudin, Rosnah; Adzahan, Noranizan; Gan, Kok Yong (2012)
The present invention relates to a UV pasteurization machine comprising: a body (100); an inlet (103) mounted on the body (100); a pump (105); UV lamps (107) vertically mounted inside the body (100); a power supply (109); an outlet (111) mounted on the body (100); a flow meter (112); and a tubing (113) connecting the inlet (103) and the outlet (111) characterized in that the tubing (113) is coiling around the UV lamps to provide maximum UV pasteurization of fruit juice which flowing inside the tubing. The above provisions are advantageous as the fruit juice is pasteurized without heating and the entire volume of the juice is effectively pasteurized due the coiling of the tubing (113) around the UV lamps (107).